2018
DOI: 10.21873/cgp.20069
|View full text |Cite
|
Sign up to set email alerts
|

Novel Germline PTEN Mutation Associated with Cowden Syndrome and Osteosarcoma

Abstract: We report a patient with CS presenting with ganglioneuromatosis, benign breast mass and osteosarcoma, harboring a novel molecular alteration in PTEN which to our knowledge has not been previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…PTEN is a tumor suppressor with phosphatase activity and decrease or loss of PTEN expression, due to the methylation, mutation or deletion, may closely relate to the occurrence and development of multiple cancers [17,18]. The clinical study found that the expression of PTEN protein in prostate cancer tissues was significantly lower than that in benign prostatic hyperplasia and negatively correlated to clinical Gleason score, pathological grade, and stage of prostate cancer [19,20], suggesting that PTEN protein decreases with the increase of the malignancy of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PTEN is a tumor suppressor with phosphatase activity and decrease or loss of PTEN expression, due to the methylation, mutation or deletion, may closely relate to the occurrence and development of multiple cancers [17,18]. The clinical study found that the expression of PTEN protein in prostate cancer tissues was significantly lower than that in benign prostatic hyperplasia and negatively correlated to clinical Gleason score, pathological grade, and stage of prostate cancer [19,20], suggesting that PTEN protein decreases with the increase of the malignancy of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Other malignant tumors include malignant melanoma [25], pituitary tumor [26], osteosarcoma [27], gastrointestinal stromal tumor [28], and dermatofibrosarcoma protuberans [29].…”
Section: N) Other Malignant Tumors and Tumorsmentioning
confidence: 99%
“…Osteosarcoma is an extremely rare presentation of PHTS (only one case has been reported in the English-written literature) [8].…”
Section: Not Reportedmentioning
confidence: 99%